2022
DOI: 10.3390/antiox11091782
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Characterization of Chinese Cabbage S1fa Transcription Factors and Their Roles in Response to Salt Stress

Abstract: The S1fa transcription factor is part of a small family involved in plant growth and development and abiotic stress tolerance. However, the roles of the S1fa genes in abiotic stress tolerance in Chinese cabbage are still unclear. In this study, four S1fa genes in the Chinese cabbage genome were identified and characterized for abiotic stress tolerance. Tissue-specific expression analysis suggested that three of these four S1fa genes were expressed in all tissues of Chinese cabbage, while Bra006994 was only exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 46 publications
2
15
0
Order By: Relevance
“…Thus, the Hg content might be increased in yeast cells, and the expression of cell wall biosynthesis genes might be activated. These findings are in line with previous studies, which reported that salt stress reduces the antioxidant enzymatic activities, enhances the ROS and MDA contents in S1fa cells and regulates the transcript level of genes involved in cell wall integrity [ 4 ]. In summary, it can be concluded that the BrCYP71A15 gene exhibits high sensitivity to Hg stress and increases Hg accumulation, which may play a key role in cell wall biosynthesis under Hg stress.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Thus, the Hg content might be increased in yeast cells, and the expression of cell wall biosynthesis genes might be activated. These findings are in line with previous studies, which reported that salt stress reduces the antioxidant enzymatic activities, enhances the ROS and MDA contents in S1fa cells and regulates the transcript level of genes involved in cell wall integrity [ 4 ]. In summary, it can be concluded that the BrCYP71A15 gene exhibits high sensitivity to Hg stress and increases Hg accumulation, which may play a key role in cell wall biosynthesis under Hg stress.…”
Section: Discussionsupporting
confidence: 93%
“…Protein Kinase C (PKC1) is regulated by BCK1p, MKK1p, SLT2p and ROM2p, which plays a fundamental role in cell wall biosynthesis, maintenance and cell integrity [ 23 , 31 ]. These findings are supported by a previous study, which reported that S1Fa OE cells regulate cell wall biosynthesis genes under salt stress in yeast [ 4 ]. Hence, it can be concluded that the BrCYP71A15 gene interacts with cell wall biosynthesis genes, and thus, Hg sensitivity is enhanced, and the accumulation of the Hg content is increased in yeast cells.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations